Fast and accurate numerical algorithm for solving stochastic Itô-Volterra integral equations - Zeghdane, Rebiha (Numerical algorithms, 2025)
The purpose of this paper is to present a simple numerical technique for approximating the solutions of stochastic Volterra integral equations. The proposed method depends on the Picard iteration and uses a suitable quadrature rule. Error estimates and associated theorems have been proved for this proposed technique. Some test examples have been studied to verify the applicability and accuracy of the proposed technique.